Analisa Fundamental Makro, Struktur Kepemilikan terhadap Nilai Perusahaan dengan Manajemen Laba, Kinerja Keuangan, Good Corporate Governance sebagai Variabel Intervening pada Perusahaan Food and Beverage di Indonesia - Ataina Rusyda Fauziyah; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2025)
The food and beverage industry in Indonesia has an important role in the national economy, but faces challenges in maintaining competitiveness and increasing firm value. This study aims to analyze the effect of macroeconomic fundamental analysis and ownership structure on firm value in the food and beverage sector, with earnings management, financial performance, GCG as intervening variables. A quantitative approach is used to identify the relationship between variables, using secondary data from the annual financial statements of companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Data analysis was carried out using Smart-PLS software. The results showed that none of the hypotheses were accepted.